Leverage, profitability, liquidity, and bond ratings: Testing the effects of company size interactions - Marseliana Marseliana; Maria Christiana Iman Kalis; Wendy Wendy; Mustarudin Mustarudin; Girang Permata Gusti (Trigin Publisher, 2023)
Bond ratings are a source of legal insurance for investors in reducing the possibility of default risk and measuring the risk of traded bonds. In this research, we examine the influence of leverage, profitability, liquidity, and company size as moderating variables on the ratings of bonds listed on the IDX. This type of research is casual with the population being manufacturing companies registered on the IDX from 2018 to 2022. Meanwhile, the research sample was determined using a purposive sampling method so that 20 sample companies were obtained. The data analysis techniques used in this research are descriptive statistical analysis, logistic regression analysis, simultaneous tests, and partial tests. Based on data processing using logistic regression, it is proven that leverage and profitability influence bond ratings with positive results. At the same time, liquidity does not significantly influence bond ratings. Leverage and liquidity, after being moderated by company size, do not significantly affect bond ratings, while profitability moderated by company size has a significant effect on bond ratings.